2018
DOI: 10.1371/journal.pone.0206174
|View full text |Cite
|
Sign up to set email alerts
|

Association of common gene variants in glucokinase regulatory protein with cardiorenal disease: A systematic review and meta-analysis

Abstract: BackgroundSmall-molecules that disrupt the binding between glucokinase and glucokinase regulatory protein (GKRP) in the liver represent a potential new class of glucose-lowering drugs. It will, however, take years before their effects on clinically relevant cardiovascular endpoints are known. The purpose of this study was to estimate the effects of these drugs on cardiorenal outcomes by studying variants in the GKRP gene (GCKR) that mimic glucokinase-GKRP disruptors.MethodsThe MEDLINE and EMBASE databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…To further examine the relationship between NAFLD and plasma sE‐selectin levels, independent of potential confounders, we studied the association of two NAFLD susceptibility genes, that is, PNPLA3 (rs738409) and GCKR (rs1260326), with plasma sE‐selectin levels in the combined CODAM and Hoorn studies (n = 1265, see Table for characteristics). Previous studies have shown that both gene variants predispose to NAFLD (including NASH) and elevated liver enzymes, but have opposing effects on factors that are associated with systemic endothelial activation, that is, plasma lipids, T2DM and coronary artery disease risk (Table ). Indeed, positive trends were observed for the relationships of the rs1260326 T‐allele ( GCKR ) and rs738409 G‐allele ( PNPLA3 ) with plasma ALT levels (β = 0.011 [95% CI: −0.004 to 0.26], P = .15; and β = 0.023 [95% CI: 0.005‐0.041], P = .01, respectively, Table ), whereas opposing effects were found for plasma triglycerides levels (β = 0.017 [95% CI: 0.006‐0.027], P = .002; and β = −0.016 [95% CI: −0.029 to − 0.004], P = .009, respectively, Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further examine the relationship between NAFLD and plasma sE‐selectin levels, independent of potential confounders, we studied the association of two NAFLD susceptibility genes, that is, PNPLA3 (rs738409) and GCKR (rs1260326), with plasma sE‐selectin levels in the combined CODAM and Hoorn studies (n = 1265, see Table for characteristics). Previous studies have shown that both gene variants predispose to NAFLD (including NASH) and elevated liver enzymes, but have opposing effects on factors that are associated with systemic endothelial activation, that is, plasma lipids, T2DM and coronary artery disease risk (Table ). Indeed, positive trends were observed for the relationships of the rs1260326 T‐allele ( GCKR ) and rs738409 G‐allele ( PNPLA3 ) with plasma ALT levels (β = 0.011 [95% CI: −0.004 to 0.26], P = .15; and β = 0.023 [95% CI: 0.005‐0.041], P = .01, respectively, Table ), whereas opposing effects were found for plasma triglycerides levels (β = 0.017 [95% CI: 0.006‐0.027], P = .002; and β = −0.016 [95% CI: −0.029 to − 0.004], P = .009, respectively, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Since individuals are ‘randomized’ at conception to receive an allele that either predisposes to or protects from NAFLD, these gene variants can serve as instruments to make causal inferences about the relationship between NAFLD and sE‐selectin levels. Although pleiotropic effects have been reported for both PNPLA3 and GCKR – which may violate this ‘Mendelian randomization’ assumption; it should be noted that these variants have opposing pleiotropic effects on plasma lipids, and risk of type 2 diabetes and coronary artery disease, as summarized in Table . As a combination, they therefore serve as a model to disentangle NAFLD from factors that affect systemic endothelial function, despite the presence of pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…By using the common variant in GCKR as a model of life-long exposure to a modest increase in hepatic glucokinase activity (Fig. 3a), it can be predicted that it will indeed result in increased de novo lipogenesis and NAFLD, as well as dyslipidaemia and CVD [51,52]. Of interest, we and others have shown that the effects of this common GCKR variant on hepatic fat accumulation and plasma triacylglycerols are more pronounced in conditions of obesity and hyperglycaemia [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…It cannot, however, be ruled out that the common variants in GCKR also have horizontal pleiotropic effects. Previous studies have shown that these variants also protect against chronic kidney disease and type 2 diabetes [50,52].…”
Section: Covariatementioning
confidence: 96%
See 1 more Smart Citation